Bacteraemia in outpatients with community-acquired pneumonia. Issue 2 (5th November 2015) - Cillóniz, Catia; Gabarrús, Albert; Almirall, Jordi; Amaro, Rosanel; Rinaudo, Mariano; Travierso, Chiara; Niederman, Michael; Torres, Antoni
Community-acquired pneumonia (CAP) is a frequent cause of morbidity and mortality worldwide. Approximately 20% of CAP patients require hospital admission [1, 2], leaving a large percentage of patients treated in the community as outpatients. In addition, bacteraemia is associated with worse outcomes, such as a higher prevalence of intensive care unit (ICU) admission and longer length of stay. Current international guidelines [1, 3, 4] do not recommend blood cultures as part of routine microbiological tests in patients managed in the community. However, there is little information regarding the prevalence and clinical impact of bacteraemia in CAP patients treated outside the hospital. Previous studies reported incidences of 2.1–7%, respectively [5–8]. However, few data exist regard predictive factors and the clinical outcomes associated with positive blood cultures in this population [8]. The current study aimed to determine the predictive factors and the clinical outcomes of bacteraemic outpatients with CAP, and describe their clinical, epidemiological and microbiological characteristics. CAP patients who are discharged but have a high risk of bacteraemia can be identified using risk factors http://ow.ly/TcMiq